Exploring the Interplay of the Impaction Type of the Mandibular Third Molar With Second Molar Distal Surface Caries - Mohammad Amir Alizadeh Tabrizi; Amir Hossein Khazaei; Maryam Khoobyari; Mahboube Hasheminasab; Sadra Amirpour Haradasht (International Journal of Dentistry, 2025)
Conclusion: High-risk patients prone to developing distal caries in the mandibular second molar should be identified to formulate a strict screening and follow-up protocol.